Ex vivo delivery of recombinant IL-10 to human donor lungs - Jonathan C. Yeung; Terumoto Koike; Dirk Wagnetz; Tiago N. Machuca; Riccardo Bonato; Mingyao Liu; Stephen Juvet; Marcelo Cypel; Shaf Keshavjee (JHLT Open)
Background: The immunoregulatory cytokine interleukin-10 (IL-10) has been shown to be a promising therapy for donor lung injuries before transplantation. However, the very short half-life of IL-10 in vivo (∼2 hours) has necessitated the use of gene therapy in almost all animal models of lung transplantation. Because isolation of the donor lung on the ex vivo lung perfusion (EVLP) circuit removes it from the influence of renal and hepatic clearance mechanisms, a much-prolonged half-life of IL-10 is anticipated. Thus, we hypothesized that delivery of recombinant IL-10 (rIL-10) to injured donor lungs isolated on EVLP could be a clinically relevant and a logistically simpler method of employing IL-10 therapy in lung transplantation. Methods: Injured human donor lungs clinically rejected for transplantation were split into single lungs and the better of the 2 subjected to 12 hours of EVLP and randomized (n = 5/group) to receive either saline (control), rIL-10 (5 µg in 2-liter perfusate), or rIL-10 (25 µg) aerosolized into the airways. Results: Perfusate and intratracheal delivery of rIL-10 did not provide the therapeutic anti-inflammatory action that has been traditionally achieved with gene therapy. It appears that intratracheally delivered rIL-10 moves into the perfusate where it seems to be biologically inactive. Conclusions: Gene therapy remains superior as it allows for continued production of IL-10 within the alveoli where it has the potential to continuously act on alveolar macrophages and epithelial cells in a paracrine fashion.